A retrospective study of concurrent radiotherapy plus S-1 for treating advanced non-small cell lung cancer. Issue 22 (June 2018) - Zhao, Dejun; Feng, Jun-fei; Wang, Xue-hui
Abstract : Abstract: We investigated the efficacy of concurrent radiotherapy plus S-1 (CRS) for treating unresectable stage III advanced non-small-cell lung cancer (ANSCLC). Seventy five ANSCLC patients were included in this retrospective study. Of those, 40 patients were assigned to an intervention group, and received S-1 (orally at 40 mg/m 2 ) twice daily for 14 consecutive days. Then, concurrent radiotherapy was administered in 2 Gy fractions, 5 times weekly for a total dose of 60 Gy. The other 35 patients were assigned to a control group, and underwent concurrent radiotherapy (the same as the intervention group) and cisplatin (60 mg/m 2 on day 1 (CRC). The outcome measurements included overall response rate (ORR), overall survival (OS), progression-free survival (PFS), and toxicity. The 3-year ORR was 60.7% and 43.9% for intervention group and control group, respectively ( P =  .031). The median OS was 34.1 months and 25.3 months in the intervention and control groups, respectively ( P =  .041). The median PFS was 31.5 months for intervention group, while it was 22.4 months for control group ( P =  .048). No significant difference in toxicity was found between the 2 groups. The results demonstrated that the efficacy of CRS was superior to the CRC in ANSCLC patients with similar toxicity.